Standard specification for stainless steel billets and bars for forging. (American Society for Testing and Materials, 2008)
This standard is issued under the fixed designation A 314; the number immediately following the designation indicates the year of original adoption or, in the case of revision, the year of last revision. A number in parentheses indicates the year of last reapproval. A superscript epsilon indicates an editorial change since the last revision or reapproval.